2016
DOI: 10.1007/s00018-016-2281-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D interferes with glucocorticoid responsiveness in human peripheral blood mononuclear target cells

Abstract: Glucocorticoids (GCs) are widely used in the treatment of inflammatory and autoimmune diseases; however, patients are often resistant to GC effects. Current studies indicate that vitamin D reduces the risk or modifies the course of autoimmune diseases posing vitamin D supplementation as a prevention or therapeutic option. Herein, we investigated whether vitamin D can modify the response to GCs at the molecular level. To this end, peripheral blood mononuclear cells (PBMCs) were isolated from healthy vitamin D-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Similar observations have been made in a squamous cell carcinoma model whereby dexamethasone induces de novo transcription of the vitamin D receptor in a glucocorticoid receptor-dependent manner (Hidalgo et al 2011). Furthermore, vitamin D also appears to have direct effects on the glucocorticoid sensitivity of peripheral blood mononuclear cells, with evidence of direct downregulation of glucocorticoid receptor expression and inhibition of GR translocation to the nucleus (Kassi et al 2016). Moreover, in patients with steroid-resistant asthma, vitamin D administration beneficially alters the clinical response to glucocorticoids (Chambers et al 2015).…”
Section: Vitamin D and Glucocorticoid Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been made in a squamous cell carcinoma model whereby dexamethasone induces de novo transcription of the vitamin D receptor in a glucocorticoid receptor-dependent manner (Hidalgo et al 2011). Furthermore, vitamin D also appears to have direct effects on the glucocorticoid sensitivity of peripheral blood mononuclear cells, with evidence of direct downregulation of glucocorticoid receptor expression and inhibition of GR translocation to the nucleus (Kassi et al 2016). Moreover, in patients with steroid-resistant asthma, vitamin D administration beneficially alters the clinical response to glucocorticoids (Chambers et al 2015).…”
Section: Vitamin D and Glucocorticoid Interactionsmentioning
confidence: 99%
“…This suggests that vitamin D homeostasis during pregnancy likely involves communication between maternal, placental and fetal compartments. Indeed, recent research has shown an interaction between vitamin D pathways and glucocorticoids ('stress' hormones) in the context of the placenta, brain, lung and other tissues (Obradovic et al 2006, Hidalgo et al 2011, Chambers et al 2015, Tesic et al 2015, Kassi et al 2016. The current review aims to discuss the potential mechanisms by which placental function may be implicated in the adverse outcomes associated with vitamin D-deficient pregnancies.…”
Section: Introductionmentioning
confidence: 96%
“…Western blot analysis was performed as previously described [16]. Briefly, whole-cell lysates were prepared in lysis buffer (Cell Signaling Technology, MA, USA).…”
Section: Sds-page and Western-blot Analysismentioning
confidence: 99%
“…We studied the effect of the long-term (11 days) repletion of vitamin D -the supplementation of which is often proposed for the prevention or even treatment of autoimmune / inflammatory diseases- on the sensitivity of peripheral blood mononuclear cells (PBMCs) to glucocorticoids [3]. …”
mentioning
confidence: 99%
“…We found that long-term action of vitamin D downregulated GILZ expression thus inducing glucocorticoid resistance in PBMCs derived from healthy volunteers. Based on our results this effect can, at least in part, be attributed to: i) decrease of glucocorticoid receptor ( GR ) expression owing to a mechanism that engages histone deacetylase(s) (HDACs), and ii) inhibition of GR translocation to the nucleus via modulation of the phosphorylation state of GR; in fact, vitamin D decreased phosphorylation of GR at Ser211 whilst enhanced phosphorylation of GR at Ser203 [3]. …”
mentioning
confidence: 99%